Comparison Of Diacerein-Ginger With Diacerein Alone In Treating Knee Osteoarthritis - Mehtab Munir; Shahid Mustafa Memon; Sajid Abbas Jaffri; Khalid Mustafa Memon (Journal of Bahria University Medical and Dental College)
Objective: To compare clinical efficacy of diacerein-ginger with diacerein alone in treating knee osteoarthritis. Duration and place of study: It was a randomized clinical trial conducted from 21st September 2018 to 31stMarch 2019, in medical OPD of a private hospital in Karachi. Methodology: 60 diagnosed patients of knee osteoarthritis were included in this study. Male and female patients 50 years of age, fulfilling the inclusion criteria and after written informed consent experienced a wash-out period of 72 hours. These patients were systematically randomized into 2 groups each having 30 members. Group A received capsule Diacerein 50mg + capsule Ginger 550 mg twice daily and group B received capsule Diacerein 50mg twice daily, for 12 weeks. Parameters checked at 0, 6 and 12 weeks were: Western Ontario and McMaster Universities Osteoarthritis (WOMAC) index, pain at rest and movement (Visual Analogue Scale). Comparison of the two groups was done by independent t-test. Results: Among 60 patients; 20 (33.33 %) were males and 40 (66.66%) were females. 4 patients in group A and 4 in B, dropped out during the study. Comparison of group A with group B in WOMAC and pain (at rest and movement) scores showed insignificant difference at day 0 before prescription of the drugs. However comparison showed highly significant difference (P-value < 0.001) between the two groups in WOMAC, pain at rest and movement scores at the end of 6th and 12th weeks of intervention. Conclusion: Diacerein-Ginger is clinically more efficacious for management of knee OA than Diacerein alone.